Strengthening the Value of Tolerance in Schools through Mathematics Subjects Based on the Independent Curriculum - Sumarno, Mahmuda; Yani T, Ahmad (STKIP Singkawang, 2023)
Mathematics learning has a very important role in human life which plays a role in structuring the reasoning and attitudes of students. This goal is supported by the implementation of the Merdeka curriculum which requires students to have a Pancasila profile character. Mathematics learning generally focuses on mastering students' cognitive competencies. The focus on instilling students' character values in certain subjects shows that teachers' awareness of the importance of character cultivation in mathematics learning is still lacking. There are still students who have not been able to accept different opinions in learning mathematics, both in the learning process and in the final results in learning mathematics. This means that students have not lived the value of tolerance contained in learning mathematics. The implementation of the Merdeka curriculum can be used as an effort to implement the value of tolerance in mathematics learning. This study aims to explore the value of tolerance of students in learning mathematics in the Merdeka curriculum through sources in the form of books and related articles. This research uses a qualitative approach with a literature study method. Implementation of the value of tolerance in the Merdeka curriculum, needs to be guided by the Pancasila learner profile as an indicator of tolerance. To strengthen the value of tolerance in mathematics learning based on the Merdeka curriculum, it can be implemented by using group learning with a guided discovery learning model which can have an impact on improving tolerance and learning outcomes